MiR‐1285‐5p/TMEM194A axis affects cell proliferation in breast cancer. Issue 2 (23rd January 2020) - Hironaka‐Mitsuhashi, Ai; Otsuka, Kurataka; Gailhouste, Luc; Sanchez Calle, Anna; Kumazaki, Minami; Yamamoto, Yusuke; Fujiwara, Yasuhiro; Ochiya, Takahiro
Abstract: The onset of breast cancer among young patients is a major issue in cancer etiology. Our previous study has shown that poor prognosis in young women with breast cancer is associated with lower expression of the microRNA miR‐1285‐5p. In this study, we showed that the expression of miR‐1285‐5p is lower in tumor tissues than in normal tissues. Accumulating evidence suggests that miR‐1285‐5p plays critical roles in various types of cancers. However, the functional role of miR‐1285‐5p in breast cancer remains to be elucidated. Here, we showed the tumor‐suppressive role of miR‐1285‐5p and detailed its mechanism of action in breast cancer. Overexpression of miR‐1285‐5p significantly inhibited cell proliferation in breast cancer cells regardless of the tumor subtype. Among the target genes of miR‐1285‐5p, we found that transmembrane protein 194A ( TMEM194A ) was directly regulated by miR‐1285‐5p. Notably, separation of centrosomes from the nuclear envelope was observed upon knockdown of TMEM194A or overexpression of miR‐1285‐5p. In conclusion, our findings show that miR‐1285‐5p is a tumor suppressor via TMEM194A inhibition in breast cancer. Abstract : We showed the tumor‐suppressive role of miR‐1285‐5p and detailed its mechanism of action in breast cancer. Overexpression of miR‐1285‐5p significantly inhibited cell proliferation in breast cancer cells regardless of the tumor subtype. We found that transmembrane protein 194A (TMEM194A) was directly regulated by miR‐1285‐5p. Our findings show that separation of centrosomes from the nuclear envelope was observed upon knockdown of TMEM194A or overexpression of miR‐1285‐5p and reveal the tumor suppressive role of miR‐1285‐5p via TMEM194A inhibition in breast cancer.